ANTECEDENTS DAN CONCEQUENCE DARI DEPENDENCY ON SMARTPHONE - Soraya, Mila; Indarini, Indarini; Setyawan, Andhy (Jurnal Manajemen, 2016)
This study aims to examine the antecedents and consequence of dependency on smartphone among university students in Surabaya. The antecedents of dependency on smartphones are Social Needs, Social Influence andConvenience, while consequence of dependency on smartphones is Purchase Behavior. This study uses purposive sampling approach, in which the sample are students in Surabaya using smartphones more than 2 years,amounted to 170 people, and is domiciled in Surabaya. We test of the model using Structural Equation Modeling with AMOS software 16. The results indicate that the Social Needs and Social Influence has a positiveand significant impact on Dependency on Smartphone. Additionally, Dependency on Smartphone has a positive influence on Purchase Behavior, whereas Convenience has positive non significant effect on Dependency onSmartphone.Keywords: Convenience, Dependency on Smartphone, Purchase Behavior, Social Needs, Social Influence